(3GdWH GdfHhis - (3CMeO Hf YHO Gddg Hf CMeO Hf ESMGb, GdMGaX,J (B432 (3g` s
(3ChdgG (B:s
(3GdYHO GdabjQ Edi Gddg JYGdi CHh HcQ Hf CMeO Hf YeQ Hf GdeSde Hf Yai Gddg Yfg hYf hGdOjg s
(3BNQgG (B:s
(3aEf GdTjWGf EPG Ccd GHf BOe GdJeQ HGdHdM ZVH hbGd YGT GHf COe s
(3QJHg Ydi SHY ebGdGJ ZjQ cGedI hHChQbGgG GdChdi JCcds
(3QhGjI CHj Ydis
(3GdMSf Hf CMeO Hf GdMSjf GdMOGO GdebQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B127 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs